Viralitas Vs Eksklusivitas: Analisis Strategi Komunikasi Digital Dalam Promosi Wisata Urban Di Surabaya - Irene Natasha; Fina Farkha; Mohammad Insan Romadhan (Journal of Media and Communication | E-ISSN : 3063-9581, 2025)
This study explores digital communication strategies in urban tourism by comparing two different destination concepts in Surabaya: Pasar Kodam Brawijaya and Graha Natura (Dream Lake). The research uses a qualitative descriptive approach with case study methods to analyze how viral and exclusive strategies are applied through social media platforms. Pasar Kodam utilizes user-generated content and viral exposure through TikTok and Instagram to reach younger audiences, while Graha Natura emphasizes curated visuals and exclusivity through controlled promotion on selected platforms. Findings indicate that viral strategies are effective in increasing mass engagement rapidly, while exclusive strategies build stronger brand identity and attract a more specific market. These insights provide a comparative understanding of how urban destinations can tailor their digital presence based on their target audience and positioning.